The Impact of Public Debt on Economic Growth: An Analysis of the Mediating Role of Inflation in Kenya - Silvester Wanyama Mackton; Robert O. Opanyi (International Journal of Economics and Financial Research, 2026)
Kenya’s escalating public debt presents a dualistic impact on economic stability. This study analyzes the debt-growth relationship from 2000 to 2024 using an integrated econometric framework comprising Autoregressive Distributed Lag (ARDL), Vector Error Correction (VECM), and Structural Equation Modeling (SEM). The analysis confirms a nonlinear relationship defined by a country-specific threshold of 47% of GDP. Beyond this inflection point, the Debt Overhang Hypothesis materializes: excessive borrowing suppresses growth by diverting critical resources toward debt-servicing obligations rather than development expenditure. While public debt facilitates long-run expansion when directed toward productive investment, Kenya exhibits heightened sensitivity to debt accumulation compared to global benchmarks. Contrary to conventional transmission models, inflation does not function as the dominant mediating channel for debt in Kenya; instead, it acts as a short-run adjustment mechanism to correct macroeconomic imbalances. The findings identify fiscal deficits as the primary driver of debt accumulation. To ensure long-term stability, Kenya must transition toward a productivity-oriented debt strategy, emphasizing disciplined borrowing, enhanced revenue mobilization, and optimized public investment efficiency.